Strengthening Legal Protection of Children's Right to Supplementary Food as a Strategic Effort for Stunting Prevention - Riyanto, Ontran Sumantri; Fuad, Fuad (LEGAL BRIEF, 2025)
Stunting prevention is a priority in improving children's health quality in Indonesia. Stunting, caused by malnutrition, impacts both the physical and mental development of children, potentially diminishing their quality of life. As a country that has ratified the Convention on the Rights of the Child, Indonesia is obligated to ensure that every child has the right to a healthy life, including access to adequate nutrition. This study aims to analyze the strategic efforts undertaken by the Indonesian government to prevent stunting. The research employs a qualitative method with a case study approach and descriptive analysis. Data are obtained through a literature review of relevant sources. This approach is used to describe and analyze the policies implemented by the Indonesian government to address stunting. The findings indicate that although regulations exist to support children's rights to nutritious food, their implementation faces various challenges, such as weak coordination between agencies and insufficient adherence to established standards. More robust law enforcement and enhanced legal capacity at the local level are crucial to ensuring the success of these policies. In conclusion, strengthening legal protection through stricter regulations and more effective monitoring will create an environment conducive to children's growth and development, thereby preventing stunting on a broader scale. This study recommends further collaboration among institutions and raising public awareness about the importance of nutritious food for children.